Role of Nijmegen Breakage Syndrome Protein in Specific T-Lymphocyte Activation Pathways - García-Pérez, Miguel Angel (American Society for Microbiology, 2001)
Nijmegen breakage syndrome (NBS) is a genetic disorder characterized by immunodeficiency, microcephaly, and “bird-like” facies. NBS shares some clinical features with ataxia telangiectasia (AT), including increased sensitivity to ionizing radiation, increased spontaneous and induced chromosome fragility, and strong predisposition to lymphoid cancers. The mutated gene that results in NBS codes for a novel double-stranded DNA break repair protein, named nibrin. In the present work, a Spanish NBS patient was extensively characterized at the immunological and the molecular DNA levels. He showed low CD3(+)-cell numbers and an abnormal low CD4(+) naive cell/CD4(+) memory cell ratio, previously described in AT patients and also described in the present report in the NBS patient. The proliferative response of peripheral blood lymphocytes in vitro to mitogens is deficient in NBS patients, but the possible link among NBS mutations and the abnormal immune response is still unknown.